Reciprocity and the Costs of Authority Relationships - Nabil I. Al-Najjar; Chris Forman (Northwestern University, Kellogg School of Management, Center for Mathematical Studies in Economics and Management Science, 1999)
Authority relationships are viewed as reciprocal exchange in which a principal offers rents in return for subordinates' compliance with his authority. These rents induce compliance by creating a collective action problem among subordinates so they free-ride on each other in challenging the principal's authority. As a consequence of the payment of these rents, the cost of exercising authority may distort the principal's ex ante choice of internal authority relationship as an organizational form, relative to market exchange or formal, arms-length contracting.
Keywords: 330